2013
DOI: 10.1371/journal.pone.0056481
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-Rich Protein 61 Plays a Proinflammatory Role in Obstructive Kidney Fibrosis

Abstract: Cysteine-rich protein 61 (Cyr61) is a secreted matrix-associated protein that regulates a broad spectrum of biological and cellular activities. This study aimed to investigate the role of Cyr61 in progressive kidney fibrosis induced by unilateral ureteral obstruction (UUO) surgery in mice. The expression of Cyr61 transcripts and proteins in the obstructed kidneys were increased from day 1 and remained high until day 10 after surgery. Immunohistochemistry indicated that Cyr61 was expressed mainly in renal tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 45 publications
4
32
1
Order By: Relevance
“…The pro-inflammatory role of CCN1 has been confirmed in independent experimental studies, demonstrating its ability to induce cytokine secretion [21,32] and to affect chemotaxis [19,20,36]. As an immediate-early gene, CCN1 is activated within minutes of cellular stimulation without requiring de novo protein synthesis [38], which may suggest that it is able to act as an upstream mediator of cytokine activation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The pro-inflammatory role of CCN1 has been confirmed in independent experimental studies, demonstrating its ability to induce cytokine secretion [21,32] and to affect chemotaxis [19,20,36]. As an immediate-early gene, CCN1 is activated within minutes of cellular stimulation without requiring de novo protein synthesis [38], which may suggest that it is able to act as an upstream mediator of cytokine activation.…”
Section: Discussionmentioning
confidence: 86%
“…Attempting to identify the potential mechanisms behind these regulations, we demonstrated that CCN1 expression in parenchymal cells is sensitive to cytokine exposure in vitro. However, accumulating evidence now suggests that CCN1 may also possess pro-inflammatory capabilities [19][20][21], indicating that this immediate early gene may be involved in the initial promotion of the inflammatory response. The present study was undertaken to investigate whether CCN1 is activated at local sites of acute tissue injury in humans and to assess its temporal relationship with the activation of the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that CCN1 may be beneficial in normal wound healing and tissue repair in contexts of resolving fibrosis but contribute to fibrosis in models of progressive fibrosis. Although the bleomycin model of lung fibrosis is known to be a slowly resolving model, we attempted to test the influence of targeting CCN1 by administering siRNA during the active fibrotic phase (d [8][9][10][11][12][13][14][15][16][17][18][19][20]. Future studies should address the effects of CCN1 in preclinical animal models of progressive fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, exogenous CCN1 or genetic overexpression resulted in regression of established fibrosis in the liver (11,12). However, in some contexts, CCN1 appears to mediate proinflammatory and profibrotic effects, for example, following ischemic kidney injury (13) or unilateral ureteral obstruction (14). In the lung, CCN1 overexpression exacerbates lung injury and causes neutrophilic alveolitis and obstructive bronchiolitis in mice (15,16).…”
mentioning
confidence: 99%
“…Increased Egr1 and Egr2 expression have been postulated as key mediators of TGFβ signaling and fibrosis and thereby as potential targets for antifibrotic therapy (47)(48)(49)(50). Cyr61, which is a member of the CTGF family, can be regulated by TGFβ and has proinflammatory properties (51,52). THBS1 is an activator of latent TGFβ so it can bind to its receptor (53).…”
Section: Continued On Next Pagementioning
confidence: 99%